2017
DOI: 10.1121/1.4983824
|View full text |Cite
|
Sign up to set email alerts
|

Binaural sensitivity in children who use bilateral cochlear implants

Abstract: Children who are deaf and receive bilateral cochlear implants (BiCIs) perform better on spatial hearing tasks using bilateral rather than unilateral inputs; however, they underperform relative to normal-hearing (NH) peers. This gap in performance is multi-factorial, including the inability of speech processors to reliably deliver binaural cues. Although much is known regarding binaural sensitivity of adults with BiCIs, less is known about how the development of binaural sensitivity in children with BiCIs compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
42
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 68 publications
(135 reference statements)
4
42
5
Order By: Relevance
“…Indeed, Gordon and colleagues initial impression was that ITD sensitivity was absent in most children with bilateral implants with similar findings from Litovsky and colleagues [26]. Weak detection of ITDs was recently reported by Gordon et al to emerge in children with over 4 years of bilateral implant experience [34].…”
Section: Direct Stimulation Of Binaural Hearingsupporting
confidence: 57%
See 2 more Smart Citations
“…Indeed, Gordon and colleagues initial impression was that ITD sensitivity was absent in most children with bilateral implants with similar findings from Litovsky and colleagues [26]. Weak detection of ITDs was recently reported by Gordon et al to emerge in children with over 4 years of bilateral implant experience [34].…”
Section: Direct Stimulation Of Binaural Hearingsupporting
confidence: 57%
“…In later work, Gordon and colleagues found that perception of ILDs was established at very early stages of bilateral implant use even for children who were older and heard through one implant for most of their lives [34]. This was consistent with findings that most children are able to discriminate stimuli containing ILD cues when tested after longer periods of bilateral implant use [26, 35]. More recently, ILD sensitivity in the envelope of short pulse trains was shown to be slightly reduced in children with long bilateral implant use (simultaneously and sequentially implanted) compared to normal hearing peers listening to clicks [34] (Figure 5A).…”
Section: Direct Stimulation Of Binaural Hearingsupporting
confidence: 52%
See 1 more Smart Citation
“…This relies on the brain's ability to process binaural spatial cues, including interaural level and interaural time differences (ILDs/ITDs) [2]. To benefit from binaural cues in everyday life, bilateral cochlear implantation is becoming increasingly common for deaf patients [3][4][5] . However, even binaural CI patients perform much below the level of normal listeners in sound localization or auditory scene analysis tasks, particularly when multiple sound sources are present [6,7].…”
mentioning
confidence: 99%
“…Under optimal conditions, normal human listeners may be able to detect ITDs not much larger than 10 μs [9]. In contrast, the ITD sensitivity of CI patients is highly variable and generally very poor, even when tested with experimental processors capable of delivering synchronized stimulus pulses with sub-millisecond resolution [3,[5][6][7]10,11].The binaural performance of CI patients depends to a fair extent on the patients' history. Importantly, pre-lingually deaf CI users invariably appear to exhibit no ITD sensitivity at all, whereas many post-lingually deaf CI users do exhibit at least some degree of ITD sensitivity [4,5,[11][12][13].…”
mentioning
confidence: 99%